Effect of carbon content in steels on the formation of the strengthened layers during thermo-deformation treatment - Hurey, Ihor; Gurey, Volodymyr; Hurey, Tetyana; Kholod, Yurii; Hera, Rostyslav (Видавництво Львівської політехніки, 2024)
The paper presents the results of forming strengthened layers on steel specimens during thermo-deformation treatment (TDT). Thermo-deformation treatment refers to surface-strengthening methods using highly concentrated energy sources. A concentrated heat flow is generated by the friction of a tool at high rates along the surface to be treated in the area of contact. After the tool moves along the treated surface, the local zone of the surface layer heated to temperatures above the phase transformation point is abruptly cooled. Shear deformation of the surface layer metal occurs in the area of contact between the tool and the treated surface. To increase the magnitude of the shear deformation, transverse grooves are made on the tool’s working surface. As the groove passes over the contact zone, the contact between the tool and the surface to be treated gets lost. This interrupts the heat flow. When the next smooth surface of the tool comes into contact, the shock load of the contact zone is transferred and the heat flow continues. A strengthened (white) layer is formed in the surface layers of the metal. It is shown that the formation of the strengthened layer is influenced by the carbon content of the studied steels. The process liquid used during treatment also has an impact. Mineral oil (MO) and an aqueous saturated solution of mineral salts based on magnesium and calcium chlorides (ASMC) were used as process liquids. In the process of thermo-deformation treatment, a tool with a smooth and discontinuous working surface was used (transverse grooves were made on the working surface). The thickness and microhardness of the layer increases with increasing carbon content. When a ASMC is used as a process liquid, the thickness and microhardness of the strengthened layer increases. The thickness and microhardness of the strengthened layer also increase when treated with a tool with transverse grooves on its working surface. The strengthened layer of the smallest thickness (80–90 µm) and microhardness (3.8 GPa) was obtained during thermo-deformation treatment of specimens made of Steel C35 (EN) with a tool with a smooth working surface using MO as a process liquid. The greatest thickness (350–370 µm) and microhardness (10.2 GPa) of the strengthened layer were obtained during the thermo-deformation treatment of specimens made of steel CT80 (EN) with a tool with a discontinuous working surface using the ASMC as a process liquid.
Keywords: surface engineering; hardening; strengthening; white layer; nanocrystalline structure; microhardness; thermo-deformation treatment; process liquid